Indigenous communities and lithium extraction in Argentina: Juridification and action strategies - Deborah Pragier; Mariano A. Novas; Lucas G. Christel (Íconos)
In Argentina, lithium mining areas coincide mostly with ancestral territories inhabited by indigenous peoples. The presence of such communities involves rights to autonomy and self-determination that easily come into tension with the interests of the state and the various companies operating in the territory. In this article, we analyze the strategies deployed by indigenous actors in the face of non-compliance with constitutionally-recognized rights. Based on a study conducted in the communities of Salinas Grandes and Laguna de Guayatayoc between 2009 and 2019, we show that in the face of unfulfilled constitutional rights, indigenous communities have deployed a cumulative and complementary strategy based on their right to self-determination. The analysis and information presented in this paper is derived from two data collection techniques: the analysis and systematization of primary and secondary documents and in-depth interviews with actors in the territory. It is concluded that in a clear context of juridification, the indigenous communities used a combination of judicial-legal action, direct action and community reinterpretation in order to demand their rights to decide respect for their territory, their ways of life and production, and their own subsistence as a community.